2021
DOI: 10.1101/2021.07.14.452084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of early or late exposure to prenatal maternal immune activation on mouse embryonic neurodevelopment

Abstract: Exposure to maternal immune activation (MIA) in utero is a risk factor for neurodevelopmental and psychiatric disorders. MIA-induced deficits in adolescent and adult offspring have been well characterized, however, less is known about the effects of MIA-exposure on embryo development. To address this gap, we performed high-resolution ex vivo magnetic resonance imaging (MRI) to investigate the effects of early (gestational day [GD]9) and late (GD17) MIA-exposure on embryo (GD18) brain structure. We identify str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, our group also demonstrated that the gestational timing of MIA-exposure could further modulate neurodevelopmental outcomes (Guma, do Couto Bordignon, et al, 2021;Guma et al, 2022;. At an even more basic level, litter-dependent modulation of body and brain weight have been reported using linear and linear mixed-effect models; these effects are further affected by sex (Golub & Sobin, 2020;Jiménez & Zylka, 2021).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, our group also demonstrated that the gestational timing of MIA-exposure could further modulate neurodevelopmental outcomes (Guma, do Couto Bordignon, et al, 2021;Guma et al, 2022;. At an even more basic level, litter-dependent modulation of body and brain weight have been reported using linear and linear mixed-effect models; these effects are further affected by sex (Golub & Sobin, 2020;Jiménez & Zylka, 2021).…”
Section: Introductionmentioning
confidence: 58%
“…Table S3.1: Detailed distribution of male and female (m:f) control pups assessed per litter and by timepoints (Guma et al, 2022).…”
Section: Chapter 5: Conclusionmentioning
confidence: 99%
“…These studies are further motivated by recent observations that offspring exposed to MIA (modeling the exposure to maternal infection during pregnancy, a known risk factor for neurodevelopmental disorders) show litter-dependent variance in resilience and susceptibility to the risk factor exposure (Mueller et al, 2021). However, our group also demonstrated that the gestational timing of MIA-exposure could further modulate neurodevelopmental outcomes (Guma, do Couto Bordignon, et al, 2021;Guma et al, 2022;. At an even more basic level, litter-dependent modulation of body and brain weight have been reported using linear and linear mixed-effect models; these effects are further affected by sex (Golub & Sobin, 2020;Jiménez & Zylka, 2021).…”
Section: Introductionmentioning
confidence: 87%